2010
DOI: 10.1159/000321713
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ERK1/2 Signaling Pathway in Coronary Microembolization-Induced Rat Myocardial Inflammation and Injury

Abstract: Aim: Inflammation plays an important role in coronary microembolization (CME)-induced myocardial injury. The present study was designed to investigate the role of extracellular signal-regulated kinases 1/2 (ERK1/2) signaling pathway in regulating myocardial inflammation and cardiac function in a rat model of CME. Methods: Sprague-Dawley rats were randomly divided into three groups: sham-operated group (sham group), CME group and PD98059 group (15 animals per group). CME was produced by injection of 42-µm micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Forty-five rats were randomized (random number) into three groups: sham, CME and CME plus TAK-242 ( n = 15 per group). The present study established a CME model by injecting plastic microspheres into the left ventricle (LV), as previously described [19, 20]. Briefly, a left lateral thoracotomy was undertaken in rats at the third and fifth intercostal space.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-five rats were randomized (random number) into three groups: sham, CME and CME plus TAK-242 ( n = 15 per group). The present study established a CME model by injecting plastic microspheres into the left ventricle (LV), as previously described [19, 20]. Briefly, a left lateral thoracotomy was undertaken in rats at the third and fifth intercostal space.…”
Section: Methodsmentioning
confidence: 99%
“…The CME model was performed as described previously. [14,15] Briefly, the rats were anesthetized with 10% chloral hydrate (3 mL/kg, i.p.) and the trachea was intubated to maintain ventilation with a respirator.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that CME-induced microinfarcts initiate an inflammatory reaction with increased tumor necrosis factor-α (TNF-α) expression [6,7], resulting in damage to the myocardium and deterioration of myocardial systolic function [8,9]. Moreover, our previous studies also verified that microinfarction and ischemia in microembolized myocardium cause a severe inflammatory response with increased TNF-α expression in concert with the impairment of cardiac function [10,11]. …”
Section: Introductionmentioning
confidence: 53%
“…Our preliminary studies showed that a post-CME inflammatory response occurred as a result of the upregulation of TNF-α expression in the myocardium [10,11]. It has been well established that excessive TNF-α expression is derived from the surviving cardiomyocytes surrounding microinfarcts in autocrine or paracrine patterns [6] and is responsible for the detrimental effect on progressive contractile dysfunction [6,7,8,20,22].…”
Section: Discussionmentioning
confidence: 99%